Priestia flexa as a Novel Urinary Tract Pathogen in Daloa, Côte d’Ivoire: Insights From Genomic Sequencing - Dého Aristide Gbégbé; Okran Beyosse Christophe Kacou; N’goran Parfait N’zi; Djédoux Maxime Angaman (International Journal of Genomics)
Bacterial strains coded 21LM367, 21LM07, and 21LM1136 were isolated from the urine of patients with urinary tract infections (UTIs) at the Centre Hospitalier Régional de Daloa in Côte d’Ivoire. Based on average nucleotide identity (ANI) analysis, DNA-DNA digital hybridisation (dDDH), and other comparative genomic methods, strains 21LM07, 21LM367, and 21LM1136 were determined to be Priestia flexa. The size of the assembled complete genomes ranged from 8,624,538 to 4,007,501 bp. The average GC content was 37.76%, 46.33%, and 43.03% for strains 21LM07, 21LM367, and 21LM1136, respectively. The total number of coding regions (CDS) in each genome was 4172, 8497, and 6795, respectively, for strains 21LM07, 21LM367, and 21LM1136. Genomic prediction analysis revealed that a total of 4241, 8583, and 6881 genes were annotated in the 21LM07, 21LM367, and 21LM1136 genomes, respectively. No virulence or resistance genes were predicted in the genomes of strains 21LM07 and 21LM1136. On the other hand, two genes conferring resistance to beta-lactam and tetracyclines as well as nine virulence genes were predicted in the genome of 21LM367. In addition, 438, 350, and 153 mobile genetic elements (MGEs) were predicted in the genomes of strains 21LM367, 21LM1136, and 21LM07, respectively. Strain 21LM07 was characterised by the absence of plasmids in its genome. Two plasmids were predicted in the genomes of isolates 21LM367 and 21LM1136; however, rep7a and IncI2 were predicted to contain the tet(K) resistance gene. No typical multilocus sequences could be characterised in the genomes of the different strains.